Structure of the C-terminal domain of the clock protein KaiA in complex with a KaiC-derived peptide: implications for KaiC regulation. - Vakonakis, I; LiWang, A (2004)
Circadian clocks are widespread endogenous mechanisms that control the temporal pattern of diverse biological processes, including gene transcription. KaiA is the positive element of the cyanobacterial clock because KaiA overexpression elevates transcription levels of clock components. Recently, we showed that the structure of KaiA is that of a domain-swapped homodimer. The N-terminal domain is a pseudo-receiver; thus, it is likely to be involved in signal transduction in the clock-resetting pathway. The C-terminal domain of KaiA is structurally novel and enhances the KaiC autokinase activity directly. Here, we report the NMR structure of the C-terminal domain of KaiA (ThKaiA180C) in complex with a KaiC-derived peptide from the cyanobacterium Thermosynechococcus elongatus BP-1. The protein-peptide interface is revealed to be different from a model that was proposed earlier, is stabilized by a combination of hydrophobic and electrostatic interactions, and includes many residues known to produce a circadian-period phenotype upon substitution. Although the structure of the monomeric subunit of ThKaiA180C is largely unchanged upon peptide binding, the intersubunit dimerization angle changes. It is proposed that modulation of the C-terminal KaiA domain dimerization angle regulates KaiA-KaiC interactions.